1978
DOI: 10.1007/bf02587790
|View full text |Cite
|
Sign up to set email alerts
|

Effect of buoyancy on the free surface flow past a permeable bed

Abstract: Abstract.Laminar steady free surface flow having one permeable bounding wall is investigated in the presence of buoyancy force. The experimental results of Rajasekhara [I] were found to be in good agreement with our theoretical results based on a model which admits slip-velocity at the porous material. The effect of buoyancy force is to increase the velocity distribution in the ease of greater heat addition (No > 0) and to decrease it by a greater cooling (No < 0). As a result, the mass flow rate increases an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…According to Rudraiah and Veerabhadraiah [18] [19], the parameter 1 β ′ denotes a constant depending on the material property of the porous medium, which have can be determined only experimentally.…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…According to Rudraiah and Veerabhadraiah [18] [19], the parameter 1 β ′ denotes a constant depending on the material property of the porous medium, which have can be determined only experimentally.…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…The condition (29) is the modified form of the temperature boundary condition developed by Rudraiah and Veerabhadraiah [7,8] and c( is an unknown constant which is a material property of the porous medium (analogous to c~ in the Beavers and Joseph [1] condition) which can be determined only experimentally on the lines similar to that of ~. See [4].…”
Section: -22flmentioning
confidence: 99%
“…At the nominal Surface, Jones condition [6] which is a modification of the velocity slip condition of Beavers and Joseph [1] for rotational flow is used to bring about the interaction between the velocity fields in the two zones. Similarly, the use of the temperature slip boundary condition at the interface developed by Rudraiah and Veerabhadraiah [7,8] brings about the interaction between the temperature fields in the two zones. While the velocity field is obtained exactly, the temperature field is computed numerically by using the Nested Numerical Quadrature Technique (NNQT) developed by Channabasappa et al [5].…”
Section: R2mentioning
confidence: 99%
“…(2/0 where u m and u B2 are the slip velocities at the upper and lower interfaces, respectively, and Q x and Q 2 are the Darcy velocities at the edge of the boundary layers, i.e., z = ± 1/2 ± \/a (see Rudraiah and Veerbhadraiah [18] where they have shown that the boundary layer is of order \/a).…”
Section: Cpfimentioning
confidence: 99%